The Options and Techniques for Pain Management in the Emergency Department, A Review Article (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study is to help emergency medicine physicians (EMPs) recognise diverse analgesic approaches so they can have access to a variety of pain treatment techniques to lessen discomfort, be able to employ them in accordance with the patient's situation, and enhance the quality of their care. The Google Scholar, Science Direct, PubMed, Medline, Scopus, and Cochrane scientific databases and search engines for emergency pain management techniques were examined in this review paper. After examining the results, high-quality studies from the years 2000 to 2018 were eventually chosen. We then compared all of the prevalent pain management techniques used in emergency departments (ED). The results are broken down into various sections under names like "Parenteral agents" and "Regional blocks" to make them easier to grasp. Acute pain is frequently treated with nonopioid analgesics such acetaminophen and nonsteroidal anti-inflammatory medications (NSAIDs). However, opioid medications are typically needed to treat acute moderate to severe pain. Regional pain blocks as part of a multimodal analgesic strategy can be beneficial when taking into account the negative effects of systemic medications and the limitations on the use of analgesics, particularly opioids. In order to help clinicians make the best decisions for patients in various clinical settings while being mindful of the limitations of the use of these analgesic medicines, this study was created to investigate and identify the advantages and downsides of using each drug.